Producing bright X-rays for imaging applications using a laser wakefield accelerator (2014)
We report on the generation of bright multi-keV betatron X-ray radiation using a GeV laser wakefield accelerator and investigate the use of these X-rays for various imaging applications. © 2014 Optical Society of America.